No Correlation Between Nasopharyngeal Human Bocavirus 1 Genome Load and mRNA Detection or Serology in Adeno-/Tonsillectomy Patients. (18th April 2019) - Ivaska, Lotta E; Christensen, Andreas; Waris, Matti; Puhakka, Tuomo; Vuorinen, Tytti; Allander, Tobias; Söderlund-Venermo, Maria; Jartti, Tuomas
Abstract: Human bocavirus 1 (HBoV1) can persist in nasopharynx and tonsils. Using HBoV1 serology, reverse-transcription polymerase chain reaction (PCR) for detecting messenger RNA (mRNA) and quantitative PCR for HBoV1 genome load count, we studied to what extent the HBoV1 DNA loads in nasopharynx correlate with acute infection markers. Tonsillar tissue, nasopharyngeal aspirate, and serum were obtained from 188 elective adeno-/tonsillectomy patients. Relatively high loads of HBoV1 DNA were detected in the nasopharynx of 14 (7%) primarily asymptomatic subjects with negative mRNA and/or serodiagnostic results. Quantitative HBoV1 DNA PCR may have lower specificity than HBoV1 mRNA detection for diagnosing symptomatic infection. Abstract : Relatively high loads of HBoV1 DNA can be detected in the nasopharynx of asymptomatic subjects with negative mRNA and/or serodiagnostic marker results. HBoV1 DNA quantitative PCR may have lower specificity than HBoV1 mRNA detection for diagnosing symptomatic infection.